The Influence of Transformational Leadership on Change Management of the NTB Mall Virtual Team Mediated by Organizational Culture - Arfatun, Arfatun; Alwyah, Lila; Syafwan, Syafwan (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
Considering the importance of responding to developments in globalization and virtual business trends, this research looks at transformational leadership in its influence on the change management of the NTB Mall virtual team which is mediated by organizational culture. This research is quantitative with a sample of 51 respondents through the distribution of questionnaires. The data was analyzed using SmartPLS software and descriptive analysis was carried out on the test result data. The research results show that transformational leadership does not significantly influence virtual team change management, transformational leadership has a positive and significant influence on organizational culture. Organizational culture has a positive and significant effect on virtual team change management, and organizational culture significantly mediates the relationship between transformational leadership and virtual team change management. Research on transformational leadership and its influence on virtual team change management through organizational culture has never been conducted in NTB, further research using organizational culture as a mediation of transformational leadership on virtual team change management has not been conducted in Indonesia, it is hoped that the research findings can be developed by further researchers by testing variables other than transformational leadership in examining its influence on organizational culture, and NTB Mall is expected to review transformational leadership in its influence on virtual team management.